Insights on the last sea urchin Diadema africanum mass mortality suggest a worldwide Diadematid pandemic in 2022-2023 - Cano, Iván; Lorenzo-Morales, Jacob; Bronstein, Omri; Sangil, Carlos; Hernández, José Carlos (Frontiers in Marine Science, 2025)
IntroductionThe sea urchin Diadema africanum, a key herbivore shaping shallow benthic ecosystems of the Canary Islands, has experienced recurrent mass mortality events (MMEs) in recent years. This study provides the first comprehensive assessment of the extent and ecological consequences of the 2022–2023 MME across the archipelago.MethodsInformation was compiled from citizen science reports, visual censuses of adult populations, and larval settlement surveys using artificial collectors and visual observations. Additionally, oceanographic data were analyzed to explore potential environmental drivers of the event.ResultsCitizen science observations revealed widespread mortality across nearly all islands, originating in the westernmost islands (La Gomera and La Palma) and spreading eastward. Visual censuses indicated severe population collapses, with adult densities decreasing by 73.8% in La Palma and 99.66% in Tenerife relative to 2021 levels—the lowest densities recorded since monitoring began. Settlement surveys in Tenerife showed a total recruitment failure in 2023, with no settlers detected in collectors and no recruits observed during visual inspections four months after the typical settlement peak.DiscussionPreliminary oceanographic analyses suggest that prolonged eastward currents and anomalous high-energy southern swells may have facilitated the initial outbreaks. The timing of this MME coincides with other Diadematid die-offs worldwide, suggesting that the Canary Islands could represent a connecting node in a potential transoceanic marine pandemic. The unprecedented population collapse and recruitment failure point to a profound disruption of the species’ life cycle, raising serious concerns about its persistence in the region and its cascading effects on ecosystem structure and function.